Entrepreneurial Orientation and Brand Orientation on Competitive Advantage: The Mediating Role Innovation Capabilities of Food Truck Entrepreneurs in Thailand - Ngammoh, Niramarn; Pitjatturat, Pongnarin; Thawiphrom, Rawitha; BoonRaum, Kaewta (Journal of Business, Innovation and Sustainability (JBIS), 2025)
The purpose of this study was to examine the connection between entrepreneurial orientation, brand orientation, innovation capabilities, and competitive advantage. Additionally, the mediating role of innovation capabilities was examined. The study followed a deductive approach based on the quantitative design in investigating the proposed relationships. Data were collected using a questionnaire. The relationships were investigated based on a sample of 176 food truck entrepreneurs using structural equation modeling (SEM). The results showed that model aligns to empirical data (CMIN/DF = 2.407, NNFI = 0.970, CFI = 0.980, SRMR = 0.056, and RMSEA = 0.073). It was also found that entrepreneurial orientation and branding orientation positively affected innovation capabilities and were directly related to competitive advantage. Entrepreneurial orientation and competitive advantage were influenced by innovation capabilities as a mediator. Innovation capabilities mediated the relationship between brand orientation and competitive advantage. Theoretical contributions made by this study contributed to a clearer understanding of the mediating role of innovation capabilities, a new phenomenon in the context of food trucks. In addition, the outcomes could be advantageous to entrepreneurs by improving the competitiveness of food truck entrepreneurs. The competitive advantage of food trucks could be affected by promoting entrepreneurial and branding orientation.